Relict Late Wisconsinan Dune Fields of the Northern Great Plains, Canada - Wolfe, Stephen; Huntley, David; Ollerhead, Jeff (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractLate Wisconsinan dune activity is investigated within the present-day boreal forest and parkland regions of the northern Great Plains, Canada, to extend the understanding of the spatial and temporal eolian record. Optical ages from stabilized sand dunes document the timing of past activity. Eolian activity ranges from about 16 ka in west-central Alberta to 9 ka in northwestern Saskatchewan. Between about 16 and 13 ka, dune activity in central Alberta occurred in an ice-proximal tundra setting along the margins of the Laurentide and Cordilleran ice sheets. Predominant dune-forming winds were from the west and northwest. Dune activity continued in this area between about 13 and 11 ka within parkland and grassland settings as the Laurentide Ice Sheet retreated to the northeast. Winds continued to blow from the west and northwest, and the climate was likely influenced by an increasingly dominant Pacific air mass. Also beginning at about 13 ka, dune-forming winds along the margins of the retreating Laurentide Ice Sheet were influenced by anticyclonic winds from the southeast that were maintained until about 9 ka. As the Laurentide Ice Sheet retreated, these southeasterly anticyclonic winds were successively replaced by winds from the northwest associated with the Pacific air mass. Dune activity across the region terminated in a time-transgressive manner from the southwest, at about 11 ka, to the northeast, at about 9 ka, with the establishment of boreal forest vegetation and reduced wind strength.